Comparative analyses of phase-detective intrusive probes in high-velocity air–water flows. (April 2017) - Felder, Stefan; Pfister, Michael
Highlights: First comparative analyses of fiber-optical and conductivity probe performances. Strong agreement of wide range of air–water flow properties for both probe types. Suitability of both systems for measurements of high-velocity air–water flows. Validation that data of previous studies collected with either system are directly comparable. Optimum dual-tip probe design has small tips positioned side-by-side. Abstract: A comparative analysis of a wide range of air–water flow properties was conducted for two types of phase-detection intrusive probes including fiber-optical and conductivity probes. Experiments were conducted on a stepped spillway model for a skimming flow discharge q = 0.478 m 2 /s and for Re = 4.7 10 5 in a flow region just downstream of the inception point of free-surface aeration and in the fully developed flow region. The comparison of a large number of key air–water flow properties showed a very close agreement for the two sensor types including void fraction, interfacial velocity and equivalent clear water flow depth enabling a direct comparison of past and future data collected with either phase-detection probe type. Minor differences were observed in terms of chord sizes, clustered properties and interparticle arrival times linked with the slightly smaller sensor size of the fiber-optical probe. The in-line positioning of the leading and trailing tips of the fiber-optical probe affected the trailing tip properties resulting in elevated turbulence intensities. An optimum dual-tip phase-detection probe design should consist of small probe tips positioned side-by-side.